Utilização da linguagem de programação C/C++ no estudo e ensino de alguns tópicos da álgebra linear - Dantas, Hian Alves (Universidade Federal Rural do Semi-Árido, 2021)
This work deals with a methodology for those who study, teach and research topics related to linear algebra. Such methodology Such methodology is effective in approaching the study of linear algebra subjects, makes use of numerical algorithms that address problems on vectors, operations with vectors, matrices and their operations, calculation of determinants, inversion of matrices and solution of linear systems. These algorithms are implemented and treated using the C\C++ programming language. This creates a mechanism capable of making the learning of this subject more practical, aiming to find more applicability to linear algebra topics directed to problems in exact and technological sciences. At the end of the work, the algorithms worked and implemented in the C/C++ programming language are shown.
Keywords: Álgebra Linear; Programação em C/C++; Algoritmo; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA